Effect of competition and sustainable financial performance aplication on the profitability at banking industry in Indonesia - Soeharjoto Soeharjoto; Debbie Aryani Tribudhi; Masni Salfinnia (Institute of Computer Science (IOCS), 2023)
The aims of this study are to determine the competition effect and the application of sustainable financial performance on the profitability of the banking industry in Indonesia. Purposive sampling was used on the Indonesian Stock Exchange in 2018-2021. The analysis used the panel data regression method. Return on Assets was used as the dependent variable, and the independent variable used banking competition and the application of sustainable financial performance, while the control variable used Net Interest Margin, Capital Adequacy Ratio, Loans to Deposit Ratio, and Non Performance Loans. For the results, the right model is used Fixed Effect effect model, with market share, economic performance, environmental performance, and Net Interest Margin having a positive and significant effect on the profitability of the banking industry, while the Herfindahl-Hirschman Index has a negative and significant effect on the profitability of the banking industry. However, governance performance, social performance, Capital Adequacy Ratio, Loans to Deposit Ratio, and Non Performance Loans have no effect on banking industry profitability.